Palm oil as the carbon source for the synthesis of carbon nanotubes using floating catalyst - chemical vapour deposition method - Mohd Zobir, Syazwan Afif; Abu Bakar, Suriani; Khusaimi, Zuraida; Mamat, Mohamad Hafiz; Zainal, Zulkarnain; Sarijo, Siti Halimah; Mahmood, Mohamad Rusop (American Institute of Physics, 2010)
CNTs were synthesized using floating catalyst by dual‐furnace thermal chemical vapour deposition method at 800–1000° C. Cooking oil made of palm oil was used as the carbon precursor. Ferrocene in the presence of 0.05 M zinc nitrate and a p‐type silicon wafer was used as a catalyst precursor and a sample target, respectively. The deposition temperature was varied from 800–1000° C. Nitrogen gas was used as a gas carrier with a constant flow rate of 150 sccm/min. Field emission scanning electron micrographs show the formation of CNTs together with other carbons formed on the silicon substrate. Raman spectroscopy studies were also supported the formation of CNTs.